1961
DOI: 10.1021/j100828a015
|View full text |Cite
|
Sign up to set email alerts
|

KINETICS OF HYDROGEN ATOM RECOMBINATION ON SURFACES1

Abstract: think, be fairly summarized by the statement that if unambiguous reaction rate constants can be found, then the quotient of the experimentally determined constants will give the equilibrium constant.Without committing them to my views, I wish to thank Drs. Wendell Forst, Benjamin Widom, John Ross, and H. 0. Pritchard for discussions and correspondence. In the light of their criticisms, the presentation has been considerably revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(53 citation statements)
references
References 2 publications
(2 reference statements)
3
48
1
Order By: Relevance
“…19 Wood and Wise reported that most metals have a fairly constant recombination probability for hydrogen radicals over a wide temperature range. 20 The surface conditions during ALD can differ from those in the reported studies, affecting the value of r.…”
Section: Plasma-assisted Aldmentioning
confidence: 77%
“…19 Wood and Wise reported that most metals have a fairly constant recombination probability for hydrogen radicals over a wide temperature range. 20 The surface conditions during ALD can differ from those in the reported studies, affecting the value of r.…”
Section: Plasma-assisted Aldmentioning
confidence: 77%
“…Note that the surface temperature can also affect the value of r, for example, a significant temperature dependence was reported for oxygen radicals on silica, 305 whereas the temperature dependence of H radicals on metals was less prominent. 306 The influence of the value of r can be illustrated by the results obtained from simple two-dimensional Monte Carlo simulations, in which the evolution of the deposition profile within a trench of high aspect ratio was studied as a function of the incoming radical flux. 304,337 This was achieved by considering only the plasma exposure step during a single ALD cycle.…”
Section: Challenges Of Plasma-assisted Aldmentioning
confidence: 99%
“…Approximately 1 out of every 5 atoms which collide with the surface undergo recombination. (The hydrogen content of the palladium was not noted during this study (27) and the efficiency may increase as the hydrogen content increases since the surface coverage increases with the bulk content.) Because of the rapid absorption which takes place via H atom generation it can be concluded that a significant fraction of the hydrogen atoms do not recombine but undergo the transition to the absorbed state.…”
Section: Discussionmentioning
confidence: 74%
“…Palladium has a very high efficiency for the H-H recombination reaction (27). Approximately 1 out of every 5 atoms which collide with the surface undergo recombination.…”
Section: Discussionmentioning
confidence: 99%